FeedNat Agro Limited: Addressing Drought through Climate Smart Seed Varieties - FeedNat Agro Limited (2024)
This is a proposal for scaling up of climate-smart seed value chain development for agricultural livelihoods resilience; a partnership between FeedNat Agro Limited and the International Management Institute (IWMI). The project aims to enhance smallholder farmer resilience to climate change by scaling up climate smart seeds of soybeans and groundnuts, coupled with capacity-building extension services and access to finance and insurance products. This intervention will provide farmers with the tools and knowledge necessary to adapt to changing climatic conditions, ensuring sustainable agriculture and stable incomes.